Prospects for the study of comorbidity in epidemiology in the post-non-classical period of science development - E. D. Savilov; S. N. Shugaeva (Эпидемиология и вакцинопрофилактика, 2022)
Revalence. There is increasingly prominent growth of joint pathology, which in some cases assumes epidemic spread in recent period of science advancement. This tendency brought along interscience relations also establishing of post-non-classical period of science development. These changes bring on developing of new concepts in scientific views on estimate of studying essentials which in previous periods of science formation primarily drawing from inter discipline check could never met in cognitive work. Aim. Assess the prospects for studying comorbidity in the post-nonclassical period of science development on the example of interdisciplinary interactions of epidemic processes of tuberculosis (TB) and HIV infection. Results. A problem-oriented study identified three main «pain points» in the integrative impact of HIV infection on the spread of TB: the simultaneous development of epidemic processes with involvement in the general population; high activity of one-stage development of both infections; and positive statistically significant correlations in the compared pairs of infectious pathology indicators. Conclusion. New data on the formation of negative trends in the TB epidemic as influenced by HIV infection are based on the basic assumptions of the post[1]nonclassical period of scientific development and are realized through an interdisciplinary approach to the study of comorbidity.